Feeling Medicine : How the Pelvic Exam Shapes Medical Training - Underman, Kelly; Underman, Kelly (Book collections on Project MUSE., 2020)
The emotional and social components of teaching medical students to be good doctorsThe pelvic exam is considered a fundamental procedure for medical students to learn; it is also often the one of the first times where medical students are required to touch a real human being in a professional manner. In Feeling Medicine, Kelly Underman gives us a look inside these gynecological teaching programs, showing how they embody the tension between scientific thought and human emotion in medical education. Drawing on interviews with medical students, faculty, and the people who use their own bodies to teach this exam, Underman offers the first in-depth examination of this essential, but seldom discussed, aspect of medical education. Through studying, teaching, and learning about the pelvic exam, she contrasts the technical and emotional dimensions of learning to be a physician. Ultimately, Feeling Medicine explores what it means to be a good doctor in the twenty-first century, particularly in an era of corporatized healthcare.